Biomineralize Mitochondria in Metal‐Organic Frameworks to Promote Mitochondria Transplantation From Non‐Tumorigenic Cells Into Cancer Cells - Zhou, Jun‐Nian; Liu, Chang; Wang, Yonghui; Guo, Yong; Xu, Xiao‐Yu; Vuorimaa‐Laukkanen, Elina; Koivisto, Oliver; Filppula, Anne M.; Ye, Jiangbin; Zhang, Hongbo (Wiley, 2025)
Mitochondria are crucial to cellular physiology, and growing evidence highlights the significant impact of mitochondrial dysfunction in diabetes, aging, neurodegenerative disorders, and cancers. Therefore, mitochondrial transplantation shows great potential for therapeutic use in treating these diseases. However, transplantation process is notably challenging due to very low efficiency and rapid loss of bioactivity post-isolation, leading to poor reproducibility and reliability. In this study, we develop a novel strategy to form a nanometer-thick protective shell around isolated mitochondria using Metal-Organic Frameworks (MOFs) through biomineralization. Our findings demonstrate that this encapsulation method effectively maintains mitochondria bioactivity for at least 4 weeks at room temperature. Furthermore, the efficiency of intracellular delivery of mitochondria is significantly enhanced through the surface functionalization of MOFs with polyethyleneimine (PEI) and the cell-penetrating peptide Tat. The successful delivery of mitochondria isolated from non-tumorigenic cells into cancer cells results in notable tumor-suppressive effects. Taken together, our technology represents a significant advancement in mitochondria research, particularly on understanding their role in cancer. It also lays the groundwork for utilizing mitochondria as therapeutic agents in cancer treatment.